Sleep Paradigm in the Qur'an Comparison of An-Nur's Tafsir and Fathul Qodir's Tafsir - Nauval Rif’an Hidayah; Wiwin Ainis Rohtih; Amir Mahmud (al-Afkar, Journal For Islamic Studies, 2025)
This research aims to examine the paradigm of sleep in the Qur'an through a comparative method (tafsir muqorain) between Tafsir An-Nur by Hasby Ash-Siddiqye and Tafsir Fathul Qodir by Imam Asy-Syaukani. The focus of this research is to analyze the concept of sleep from several key verses, namely: QS. An- Naba’ : 9, QS. Az- Zumar : 42, QS. Al – Isra’ : 79. This study is very important because sleep is not just a biological phenomenon, but also has spiritual significance in Islam, where the Qur'an views sleep as a sign of God's power, a form of mercy, and a time for worship. The method used is muqorain interpretation, comparing the interpretations of both mufassir regarding the verses that discuss sleep. This approach allows researchers to explore the tendencies of both interpreters by comparing their backgrounds, scholarly expertise, and other factors. The research results show a difference in the approach of the two mufassir, where Hasby tends to prioritize a contextual modernist approach, while Asy-Syaukani emphasizes a classical textual approach. Both approaches contribute to enriching the understanding of the concept of sleep in Islam, both from physiological and spiritual aspects. The conclusion of this research emphasizes that the muqorain method is not only relevant for understanding the diversity of interpretations but also beneficial in building critical awareness of various perspectives. Through the comparison of interpretations, this research presents a more holistic understanding of the concept of sleep in the Qur'an, making it applicable in the context of modern life.